Assessment of Waste Cooking Oil Biodiesel as a Sustainable Fuel: Combustion and Performance Evaluation in a CI Engine - Sharma, Shahil; Karn, Rupesh Lal (International Journal on Engineering Technology, 2025)
This study presents a comprehensive evaluation of waste cooking oil biodiesel blends (10%, 20%, and 25% by volume) in a single-cylinder, water-cooled diesel engine operating at constant 1500 rpm under varying load conditions. FTIR spectroscopy revealed characteristic biodiesel signatures, including strong ester carbonyl absorption at 1740 cm⁻¹ and weaker hydrocarbon peaks (2800-3000 cm⁻¹) as compared to diesel. The biodiesel, synthesized through optimized transesterification (0.85% KOH catalyst, 6:1 methanol-to-oil ratio, 60°C reaction temperature, 600 rpm agitation speed, and 1-hour duration), exhibited key fuel properties including a calorific value of 38.45 MJ/kg and viscosity of 4.5 cSt. So, pure biodiesel is not recommended for this engine without modifications. Performance analysis revealed that while the 25% blend achieved 12.57% higher indicated power at 4 kW brake power compared to diesel, it suffered a 9.60% reduction in mechanical efficiency and a 19.61% decrease in brake thermal efficiency. The specific fuel consumption increased progressively with blend ratio, reaching 36.94% higher values for the 25% blend relative to diesel. Combustion characterization demonstrated significant differences, with peak cylinder pressure increasing by 5.77% (72.4 bar vs. 68.5 bar for diesel) and ignition delay shortening by 2.1 crank angle degrees for the 25% blend at full load conditions. The cumulative heat release rose by 5.93%, while net heat release decreased by 12.40% due to elevated exhaust gas temperatures that were 42.29% higher than diesel. Notably, the 20% blend emerged as the optimal compromise, delivering a 3.62% increase in peak cylinder pressure (63.2 bar) with only a 7.01% mechanical efficiency penalty. The smoke emissions from every fuel blend tested fell below the maximum level permitted by the ISO 11614 standard, confirming their environmental safety. These findings provide critical insights into the trade-offs between enhanced combustion characteristics and reduced thermal efficiency when utilizing WCO biodiesel blends in conventional diesel engines